2021
DOI: 10.1039/d1ja00288k
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the ability of triple quadrupole inductively coupled plasma mass spectrometry for the determination of Pu isotopes in environmental samples

Abstract: The monitoring of Pu isotopes in environmental samples was essential for radioactive assessment and tracing the geochemical processes. Triple quadrupole inductively coupled plasma mass spectrometry (ICP-MS/MS) has shown strong ability...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…The results showed that although the measured 238 U count rates in sample solution separated using single AG1-× 4 anion exchange resin column (5470 cps for IAEA-385 and 6870 cps for IAEA-327) were nearly 1 order of magnitude higher than those using the TEVA column and the combination of the AG1-× 4 anion exchange and TEVA columns (<1100 cps for IAEA-385 and <390 cps for IAEA-327), the contributions of 238 U to 239 Pu signals for the single AG1-× 4 column separation procedure were <1 cps, which was at least two orders of magnitude lower than that the count rates at m/z = 239 in the prepared samples. There were no significant discrepancies among the analytical results of 240 Pu/ 239 Pu atomic ratios (0.9% for IAEA-385 and 1.6% for IAEA-327) and concentrations of 239 Pu (1.3% for IAEA-385 and 7.5% for IAEA-327), 240 Pu (1.2% for IAEA-383 and 9.6% for IAEA-327) and 241 Pu (4.1% for IAEA-385 and 11.3% for IAEA-327) for the two reference materials treated with the different chemical procedures, and all the measured values for the IAEA-385 and IAEA-327 agreed well with their certificated values [27] and literature reported values [21,28,29]. These results indicated that the one stage separation procedure using the anion-exchange chromatography combined with the developed ICP-MS/MS detection method should be reliable for the accurate measurement of low-level plutonium isotopes in environmental samples with small sample amount (<2 g).…”
Section: Performance Evaluation For Determining Pu Isotopes In Reference Materials and Environmental Samples Treated By Different Chemicasupporting
confidence: 84%
See 2 more Smart Citations
“…The results showed that although the measured 238 U count rates in sample solution separated using single AG1-× 4 anion exchange resin column (5470 cps for IAEA-385 and 6870 cps for IAEA-327) were nearly 1 order of magnitude higher than those using the TEVA column and the combination of the AG1-× 4 anion exchange and TEVA columns (<1100 cps for IAEA-385 and <390 cps for IAEA-327), the contributions of 238 U to 239 Pu signals for the single AG1-× 4 column separation procedure were <1 cps, which was at least two orders of magnitude lower than that the count rates at m/z = 239 in the prepared samples. There were no significant discrepancies among the analytical results of 240 Pu/ 239 Pu atomic ratios (0.9% for IAEA-385 and 1.6% for IAEA-327) and concentrations of 239 Pu (1.3% for IAEA-385 and 7.5% for IAEA-327), 240 Pu (1.2% for IAEA-383 and 9.6% for IAEA-327) and 241 Pu (4.1% for IAEA-385 and 11.3% for IAEA-327) for the two reference materials treated with the different chemical procedures, and all the measured values for the IAEA-385 and IAEA-327 agreed well with their certificated values [27] and literature reported values [21,28,29]. These results indicated that the one stage separation procedure using the anion-exchange chromatography combined with the developed ICP-MS/MS detection method should be reliable for the accurate measurement of low-level plutonium isotopes in environmental samples with small sample amount (<2 g).…”
Section: Performance Evaluation For Determining Pu Isotopes In Reference Materials and Environmental Samples Treated By Different Chemicasupporting
confidence: 84%
“…In addition to the above strategies, the collision-reaction cell (CRC) technology has widely been applied to ICP-MS (e.g., triple quadrupole ICP-MS) as a straightforward means [15,18] to eliminate uranium interferences for measurement of plutonium isotopes. The CRC with the application of different collision/reaction gases (e.g., NH 3 -He, CO 2 , O 2 ) has shown its ability to effectively remove uranium interferences by more than 15 times compared to the conventional ICP-MS [15,[19][20][21]. Although O 2 and CO 2 as reaction gases could effectively eliminate the interferences of uranium and its hydrides by converting to oxides of uranium ions, part of Pu could also react with these gases so that the intensity of the Pu signal was less than 3400 Mcps/(mg/L) even if the ICP-MS was equipped with a high-efficiency desolvation system (e. g, APEX-Q/Ω) [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…By using this system, the residual solvent of the sample was removed, and thus ‘dry’ plasma was generated. 23 The N 2 and Ar flow rates for the sample introduction system were set to be 4 mL min −1 and 3.25 L min −1 , respectively. Coupled with the TQP-50-A0.5 nebulizer (200 mL min −1 ), the sensitivity of the instrument for 99 Tc was improved to 5000 cps ppt −1 in the MS/MS detection mode.…”
Section: Resultsmentioning
confidence: 99%
“…Triple quadrupole ICP-MS is becoming a key tool in environmental isotopic analysis and Bu et al 186 utilised this technique to determine Pu isotopes in low-level soil RMs. A key benefit of this instrumentation is the gas reaction cell, and in this study mixed NH 3 –He (proportioned 1 : 9) was used to remove UH + interference on 239 Pu while retaining suitable sensitivity of Pu.…”
Section: Isotope Analysismentioning
confidence: 99%